Model Pendidikan Guru Berbasis Ke-Bhinekaan Budaya di Indonesia - Al Musanna (Jurnal Pendidikan dan Kebudayaan, 2011)
Teacher education in Indonesia should give more attention to the revitalization of local cultures as the foundation. It is based on the fact that Indonesia is one of the most pluralistic nations in terms of ethnicity and culture. The praxis of culturally responsive teacher education promise solution to bridge the revitalization of local culture and to improve the relevance of teacher education in Indonesian context. Preparing teacher to be a culturally competent teacher can be solutions to marginalization an alienation of many aspects of local culture in Indonesian educational policy.